2021
DOI: 10.31557/apjcp.2021.22.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac, Hepatic and Renal Dysfunction and IL-18 Polymorphism in Breast, Colorectal, and Prostate Cancer Patients

Abstract: Introduction:The present study aimed to determine the alterations in the serum levels of tumor markers used to evaluate cardiac, renal and liver function, and detect the interleukin (IL)-18 rs1946518 polymorphism in breast (BC), colorectal (CRC) and prostate cancer (PCa) patients. Methods: Blood samples were collected from 65 female BC, 116 CRC, 79 PCa and 88 myocardial infarction (MI) patients, and 110 healthy individuals to determine the concentration of tumor and cardiac markers. Furthermore, the IL-18 rs19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Yet to date, the sole Food and Drug Administration (FDA)-approved PDAC biomarker remains serum carbohydrate antigen (CA) 19-9. CA19-9 has limited disease specificity as levels can be elevated in several other concomitant conditions (eg, biliary obstruction) and is therefore mostly used as a marker for PDAC surveillance, rather than screening or diagnosis 10–14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet to date, the sole Food and Drug Administration (FDA)-approved PDAC biomarker remains serum carbohydrate antigen (CA) 19-9. CA19-9 has limited disease specificity as levels can be elevated in several other concomitant conditions (eg, biliary obstruction) and is therefore mostly used as a marker for PDAC surveillance, rather than screening or diagnosis 10–14…”
Section: Introductionmentioning
confidence: 99%
“…CA19-9 has limited disease specificity as levels can be elevated in several other concomitant conditions (eg, biliary obstruction) and is therefore mostly used as a marker for PDAC surveillance, rather than screening or diagnosis. [10][11][12][13][14] PDAC has a complex aetiology, with established risk factors that include age, chronic pancreatitis, diabetes mellitus, obesity, asthma, blood group and lifestyle (eg, smoking and heavy alcohol consumption). 15 16 The role of these risk factors in PDAC aetiology may also be complemented-or sometimes indeed mediated-by alterations in the microbiome.…”
Section: Introductionmentioning
confidence: 99%
“… 34 A case–control study including 194 patients with prostate cancer and 210 controls did not find evidence for an association between ALT and risk of prostate cancer (mean ± SD: 20.08 ± 10.87 vs 21.71 ± 13.21), 10 whereas another cross-sectional study reported that prostate patients with poorly differentiated tumors had a higher ALT level (0.35ukat/l vs 0.39ukat/l) than had patients with well-differentiated clinical prostate cancer, 29 and Govand et al indicated that the activity of ALT was higher in patients with prostate cancer compared with controls (median and range, 16.25:11.38–29.05 vs 17.1:11.33–31.75). 9 These conflicting findings from conventional observational studies may because that these studies are susceptible to biases, such as reverse causation and residual confounding (eg, cancer staging, dietary, or molecular factors), which may confound the observational association estimates between ALT and prostate cancer. Nevertheless, evidence from a meta-analysis reported an inverse association between circulating levels of ALT and risk of overall cancer in European populations (RR per 1 SD=0.96, 95% CI: 0.94–0.99), 35 suggesting that ALT may be involved in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In addition, transaminases, such as alanine aminotransferase (ALT), were found to be markedly elevated in serum samples from patients with prostate cancer, compared with controls. 9 However, Zhou et al reported that there were no differences in the serum levels of ALT in patients with prostate cancer compared with those diagnosed with benign prostatic hyperplasia. 10 Since the above findings were from traditional observational epidemiological studies, which may be vulnerable to bias such as confounding and reverse causation, it remains unclear whether these AAs and transaminases are causally associated with the risk of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…87). IL-18-rs1946518, IL-18-607 and IL18-137 gene polymorphisms were significantly correlated with increased risk of BC (Refs 88, 89, 90, 91). It's also worth mentioning that IL-18 was overexpressed in tumour samples (Refs 92, 93), plasma (Ref.…”
Section: What Are Inflammasomes?mentioning
confidence: 98%